Depressive symptoms mediate the longitudinal association between diabetes and subjective cognitive decline. Findings from a semirural multi-ethnic older population in Malaysia - Johar, Hamimatunnisa; Schaefer, Alexandre *; Su, Tin Tin (Elsevier, 2023)
The potential role of psychological distress as the pathway linking diabetes and subjective cognitive decline (SCD) is still unclear. This study aims to investigate whether depressive symptoms mediate the relationship between diabetes and SCD in older adults. Baseline data from 3428 adults (55-94 years) of the South East Asia Community Observatory (SEACO), Malaysia were utilized. Subjective cognitive complaints (SCC) were recorded at baseline and five years later. Mediation analyses with non-parametric bootstrapping methods were employed. A proportion of 20% of participants without SCC at baseline reported a decline in SCC after 5 years of follow-up. Known diabetes (β = -0.13, SE = 0.05, p = 0.02) and depressive symptoms (ß = -0.18, SE = 0.05, p = 0.001) were independently associated with SCD. Previously diagnosed diabetes was associated with depressive symptoms at baseline (ß = 0.04, SE = 0.02, p = 0.01), and greater SCD at follow-up (β = -0.19, SE = 0.06, p = 0.001). Mediation analyses revealed that 9% of the association between diabetes and SCD was attributable to an indirect effect through depressive symptoms (ß = -0.01, 95% CI 0.02-0.001, p < 0.0001). This study provides further evidence of the detrimental effects of diabetes and depression on subjective cognitive decline. Our findings also suggest that depression is an important pathway linking previously diagnosed diabetes with subjective cognitive decline in older adulthood.